2012
DOI: 10.3748/wjg.v18.i21.2682
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening: Comparison of transferrin and immuno fecal occult blood test

Abstract: Tf dipstick test might be used as an additional tool for CRC and precancerous lesions screening in a high-risk cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Previous studies from China [14][15][16] presented similar diagnostic performance of fecal hemoglobin and transferrin among symptomatic individuals at increased risk. In all three studies the combination of both markers led to an increase of sensitivity for CRC from 75% to 90%, 14 from 96% to 100%, 15 and from 57% to 86%, 16 respectively, but this went along with a similarly strong reduction of specificity from 88% to 71%, 14 from 72% to 61%, 15 and from 59% to 38%, 16 respectively. Because no AUCs were calculated, it was unclear whether the combination of both markers is able to improve the overall test performance, especially among average-risk screening participants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies from China [14][15][16] presented similar diagnostic performance of fecal hemoglobin and transferrin among symptomatic individuals at increased risk. In all three studies the combination of both markers led to an increase of sensitivity for CRC from 75% to 90%, 14 from 96% to 100%, 15 and from 57% to 86%, 16 respectively, but this went along with a similarly strong reduction of specificity from 88% to 71%, 14 from 72% to 61%, 15 and from 59% to 38%, 16 respectively. Because no AUCs were calculated, it was unclear whether the combination of both markers is able to improve the overall test performance, especially among average-risk screening participants.…”
Section: Discussionmentioning
confidence: 76%
“…13 Previous studies suggested that combining FITs for hemoglobin with fecal transferrin might increase sensitivity among symptomatic individuals. [14][15][16] For example, Sheng et al reported an increase of sensitivity for CRC and advanced adenoma (AA) from 75% to 90% and from 44% to 78%, respectively. 14 Transferrin is an iron-binding blood plasma protein that is released together with hemoglobin through bleeding into the digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…Transferrin (Tf), which is mainly responsible for the transport of iron in the blood, has also been identified as a potential biomarker for CRC [14] , [15] . Bleeding into the gastrointestinal tract releases both Tf and Hb into feces where it can be measured by immunoassay-based tests [15] , [16] , [17] , [18] . Furthermore, it has been reported from in vitro studies [15] , and implied from studies done on CRC screening populations [17] , that Hb is more sensitive to degradation by enterobacteria and digestive enzymes than Tf.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding into the gastrointestinal tract releases both Tf and Hb into feces where it can be measured by immunoassay-based tests [15] , [16] , [17] , [18] . Furthermore, it has been reported from in vitro studies [15] , and implied from studies done on CRC screening populations [17] , that Hb is more sensitive to degradation by enterobacteria and digestive enzymes than Tf. While the original source of data substantiating the latter claim is not clear, it has been hypothesized that increased time in the bowel due to constipation or bleeding from lesions located further up the bowel in the ascending colon may yield false negative results when Hb is used alone as a screening biomarker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation